2010
DOI: 10.1016/j.exer.2010.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of streptozotocin-induced microvascular changes in the mouse retina with the endothelin receptor A antagonist atrasentan

Abstract: Hyperglycemia mediates endothelial cell dysfunction through a number of potential mechanisms that could result in the decrease of retinal blood flow early in diabetes. The aim of this study was to explore the role of endothelin receptor A (ETA) in the early decrease of retinal blood flow in diabetic mice. Diabetes was induced by streptozotocin, then ~1 wk later the mice were administered drinking water with or without the ETA receptor antagonist atrasentan (7.5 mg/kg/day) for the following 3 weeks. Non-diabeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 17 publications
(22 reference statements)
4
50
2
1
Order By: Relevance
“…They are also similar to other reported reductions in F values in STZ-diabetic mice. 3236 Had these investigators measured O 2A , it is likely that they would have found decreases in DO 2 similar to the decrease of 43% in the current study. These defective DO 2 and F responses in diabetes likely correspond to the well-known impaired autoregulation seen in humans with diabetes.…”
Section: Discussionsupporting
confidence: 60%
“…They are also similar to other reported reductions in F values in STZ-diabetic mice. 3236 Had these investigators measured O 2A , it is likely that they would have found decreases in DO 2 similar to the decrease of 43% in the current study. These defective DO 2 and F responses in diabetes likely correspond to the well-known impaired autoregulation seen in humans with diabetes.…”
Section: Discussionsupporting
confidence: 60%
“…Other vasoconstricting pathways also are likely to be involved, and we have obtained evidence for contributing roles of thromboxane, angiotensin II, and endothelin-1. [3][4][5] However, the extent of overlap between these vasoconstrictors with the mechanisms induced by reactive oxygen species has yet to be determined, although there is evidence of a significant link between angiotensin II and oxidative stress. 19 Tempol may enhance the effects of the vasodilator nitric oxide (NO) by several mechanisms, as reviewed by Wilcox and Pearlman 7 : (1) by preventing the bioinactivation of NO by superoxide, (2) by enhancing shear-induced endothelial production of NO, (3) by interrupting the incorporation of NO into glutathione to form S-nitrosoglutathione, (4) by increasing the activity of the redox-sensitive dimethylarginine dimethylaminohydrolase, which inactivates the NO synthase inhibitor asymmetric dimethylarginine, and (5) by improving the availability of the reduced form of tetrahydrobiopterin and thereby recoupling NO synthase.…”
Section: Discussionmentioning
confidence: 98%
“…7 Studies from other labs have demonstrated significant diabetes-induced increases in superoxide production in mice and rats early in the progression of disease. [8][9][10][11][12] In studies from our lab, we see a decrease in retinal blood flow occurring as early as 3-4 weeks following induction of diabetes, [3][4][5]13 and herein test the hypothesis that tempol administration may attenuate this decrease.…”
Section: Introductionmentioning
confidence: 92%
“…Some studies in diabetic mice show that there is an initial decrease in retinal blood flow between three to 4 weeks due to arteriolar constriction, however arteriolar diameter and blood flow return to normal measurements at later time points of diabetes (12 weeks) [49][50][51][52]. Despite the initial decrease in blood flow these studies did not find any evidence of hypoxia in these animals at either 3 or 12 weeks of diabetes [53][54][55].…”
Section: Oxygen Supply and Consumption In The Healthy Retinamentioning
confidence: 58%